أهمية الاشتقاق وتعليمه في تطور اللغة العربية - Inayatur Rosyidah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2019)
The concept of Arabic derivation (Isytiqaq) is a very important study of Arabic. Arabic has morphological tools that form derivations. These tools are called binyan (wazan). In addition, the derivation of Arabic has meaning and function regarding the Arabic language itself. Changes in function and meaning that occur because of a change that is the basic verb into derivational verbs from each verb earlier derived various nouns. Arabic derivation which includes morphology, qolb, ibdal and acronyms has contributed a lot to the Arabic vocabulary in order to support the development of Arabic, so that new terms in the vocabulary in Arabic are also increasingly diverse.